Innovation in Disaster Learning Media Management in the Classroom - Kamaruddin, Syamsu A. (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This paper aims to reveal the creativity of lecturers in media learning management in the classroom. The research was conducted by the survey to the students of the Sociology section of Makassar State University of 49 students as respondents by using the Quota Sampling technique. They have distributed questionnaires about the creativity of the lecturers in the course of introducing sociology in the management of learning media. The data analysis using the tabulation frequent, and reinforced by interview results. The result of the research shows (1) the creativity of the lecturers to manage the learning media in the good category, (2) Inhibiting factors of learning media management are technical aspect, such as: internet network disruption, LCD projector damage, and students do not carrying laptop and charger.